2012
DOI: 10.1088/1742-6596/343/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Immirzi parameter and Noether charges in first order gravity

Abstract: The framework of SO(3, 2) constrained BF theory applied to gravity makes it possible to generalize formulas for gravitational diffeomorphic Noether charges (mass, angular momentum, and entropy). It extends Wald's approach to the case of first order gravity with a negative cosmological constant, the Holst modification and the topological terms (Nieh-Yan, Euler, and Pontryagin).Topological invariants play essential role contributing to the boundary terms in the regularization scheme for the asymptotically AdS sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…[35,36] in first-order formalism. In this Riemann-Cartan approach, the parity-violating sector appears enlarged by the Holst and Nieh-Yang terms, which are identically vanishing in Riemannian gravity [37].…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] in first-order formalism. In this Riemann-Cartan approach, the parity-violating sector appears enlarged by the Holst and Nieh-Yang terms, which are identically vanishing in Riemannian gravity [37].…”
Section: Discussionmentioning
confidence: 99%
“…which can be expanded in orders of 1/r, with [3] To reiterate, the criterion for fixing Λ ab in the asymptotic case is very different to that used in the global case. In the former case, the criterion is that once a vierbein has been 6 To be clear, δ ξ E i I represents an explicit transformation of the metric component functions that appear in E i I using the prescription derived from δ ξ gµν = L ξ gµν . In particular, δ ξ Êi I = 0.…”
Section: Asymptotic Symmetries In the Tetrad Formalismmentioning
confidence: 99%
“…[3], it was shown that asymptotic BMS charges derived from such terms would be subleading at null infinity. Higher derivative terms have been considered in various settings in the literature [4][5][6][7][8][9][10][11]. While the importance of higher derivative terms has been stressed in much of the literature connected to the Anti-de Sitter case starting with Ref.…”
Section: Introductionmentioning
confidence: 99%
“…R − and Barbero-Immirzi parameter γ ∈ R \ {0} on a four-dimensional manifold (M, e, A) with generic boundary ∂M is [1][2][3][4]:…”
mentioning
confidence: 99%
“…g ab = η IJ e I a ⊗ e J b and Ω I J = dA I J + A I K ∧ A K J = (1/2)R I JKL e K ∧ e L , with R I JKL being the Riemann tensor. The first-order Holst action with negative cosmological constant Λ := −3ℓ −2 ∈ R − and Barbero-Immirzi parameter γ ∈ R \ {0} on a four-dimensional manifold (M, e, A) with generic boundary ∂M is [1][2][3][4]:…”
mentioning
confidence: 99%